2017
DOI: 10.1038/ncomms13957
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 6 contributes to autoimmunity in lupus-prone mice

Abstract: Expansion of autoreactive follicular helper T (Tfh) cells is tightly restricted to prevent induction of autoantibody-dependent immunological diseases, such as systemic lupus erythematosus (SLE). Here we show expression of an orphan immune regulator, death receptor 6 (DR6/TNFRSF21), on a population of Tfh cells that are highly expanded in lupus-like disease progression in mice. Genome-wide screening reveals an interaction between syndecan-1 and DR6 resulting in immunosuppressive functions. Importantly, syndecan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…This is reminiscent of death receptor 6, a member of the TNF receptor superfamily. Full-length DR6 can act as a surface receptor transmitting cell death signals (Nikolaev et al, 2009;Mi et al, 2011;Strilic et al, 2016;Fujikura et al, 2017;Gamage et al, 2017), while the ADAM10-cleaved DR6 ectodomain can act as a cytokine suppressing proliferation of Schwann cells and delaying myelination in the peripheral nervous system (Colombo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is reminiscent of death receptor 6, a member of the TNF receptor superfamily. Full-length DR6 can act as a surface receptor transmitting cell death signals (Nikolaev et al, 2009;Mi et al, 2011;Strilic et al, 2016;Fujikura et al, 2017;Gamage et al, 2017), while the ADAM10-cleaved DR6 ectodomain can act as a cytokine suppressing proliferation of Schwann cells and delaying myelination in the peripheral nervous system (Colombo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Tagging syndecan constructs at the C-terminus interferes with their correct processing and targeting (Maday et al, 2008), and tagging at the N-terminus may also interfere with syndecan functions since the major ligand-binding HS chains are attached near the N-terminus in all four syndecans. However, syndecan-1 His-tagged at the N-terminus has been shown to retain its ability to bind to death receptor 6 (Fujikura et al, 2017), suggesting that N-terminal tagging may not interfere with activity, although the activity and HS structure of tagged syndecan-1 were not rigorously compared to those of the native counterpart.…”
Section: Isolation Of Syndecansmentioning
confidence: 99%
“…DR6 is also expressed in oligodendrocytes, which are the myelinating cells in the CNS. Additionally, DR6 controls proliferation and differentiation of immune cells (Zhao et al, 2001;Schmidt et al, 2003;DeRosa et al, 2008), and was recently shown to contribute to tumor cell-induced endothelial cell necroptosis and autoimmunity in lupus-prone mice (Strilic et al, 2016;Fujikura et al, 2017). Consequently, DR6 has been linked to Alzheimer's disease and is considered as a drug target for multiple sclerosis (Nikolaev et al, 2009;Mi et al, 2011;Kallop et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, DR6 has been linked to Alzheimer's disease and is considered as a drug target for multiple sclerosis (Nikolaev et al, 2009;Mi et al, 2011;Kallop et al, 2014). Additionally, DR6 controls proliferation and differentiation of immune cells (Zhao et al, 2001;Schmidt et al, 2003;DeRosa et al, 2008), and was recently shown to contribute to tumor cell-induced endothelial cell necroptosis and autoimmunity in lupus-prone mice (Strilic et al, 2016;Fujikura et al, 2017). In these processes, DR6 acts cell-autonomously as a membrane-bound receptor, similar to the central nervous system.…”
Section: Introductionmentioning
confidence: 99%